LH signaling induced ptgs2a expression is required for ovulation in zebrafish. (15th May 2017) - Tang, Haipei; Liu, Yun; Li, Jianzhen; Li, Gaofei; Chen, Yu; Yin, Yike; Guo, Yin; Cheng, Christopher H.K.; Liu, Xiaochun; Lin, Haoran
Abstract: It is well known that ovulation is induced by luteinizing hormone (LH) surge. However, the down-stream factors that mediating LH surge induced ovulation are less clear. The cyclooxygenases (also known as PTGS ) as key enzymes for prostaglandins synthesis appear to be important for ovulation in mammals, but their functional roles and molecular mechanism in regulation of fish ovulation are largely unexplored. In this study, we have systematically investigated the expression, regulation and functional roles of cox genes during zebrafish ovulation. Three types of cox genes including ptgs1, ptgs2a and ptgs2b have been identified in zebrafish. The ptgs2a was dominantly expressed in the ovary with a maximal level at the maturation stage of the follicles. In addition, the ptgs2a expression is up-regulated by LH signaling in vitro and in vivo . Moreover, co-injection of a selective Ptgs2 inhibitor and non-selective Ptgs inhibitor with hCG could significantly block the stimulatory effect of hCG induced ovulation in vivo . Collectively, our findings indicate that LH signaling induced ptgs2a expression is required for ovulation in zebrafish. Highlights: Of the three zebrafish cox genes, the ptgs2a is most dominantly expressed in the ovary with a maximal level at M stage. The ptgs2a expression is significantly higher in the follicular cells layers than the oocyte. The ptgs2a expression is regulated by LH signaling through the cAMP-PKA pathway. Co-injection of the Ptgs2 inhibitor with hCG could block the hCG-induced ovulation.